Interfacial manipulations controlling nanoscale assembly in bulk, thin film, and solution block copolymer systems - Mastroianni, Sarah E (Langmuir : the ACS journal of surfaces and colloids, 2013)
Nanostructured soft materials from self-assembled block copolymers (BCP)s and polymer blends can enable the reliable, high-throughput, and cost-effective generation of nanoscale structural motifs for many emerging technologies. Our research group has studied the phase behavior of BCPs in bulk, thin film, and solution environments with a particular focus on using interfacial manipulations to control self-assembly and to access a vast array of nanoscale morphologies and orientations. These interfacial manipulations can be synthetic alterations that are directly incorporated into the BCP chain to modify polymer-polymer interactions, post-polymerization and non-synthetic modifications that affect block interactions, or changes to the polymer specimen's external surroundings to control self-assembly in a confining environment. Herein, we describe methods that we have employed to manipulate BCP self-assembly for various application targets, and we discuss the key effects of such manipulations on the resulting nanoscale morphologies